Of Blood and Bone - Roberts, Nora; Whelan, Julia 1984- (Grand Haven, MI : Brilliance Audio, Inc., 2018)
Fallon Swift, approaching her thirteenth birthday, barely knows the world that existed before. Those like Fallon, in possession of gifts, are hunted, and the time is coming when her true nature, her identity as The One, can no longer be hidden. Her training is about to begin and she will find powers within herself she never imagined. When the time is right, she will take up the sword, and fight. For until she grows into the woman she was born to be, the world outside will never be whole again.
Keywords: Witches -- Fiction; Vampires -- Fiction; Magic -- Fiction; Paranormal fiction; Domestic fiction; Audiobooks